Discretion of Government Officials Detrimental to State Finances: The Intersection Between Administrative Illegality and Criminal Illegality - Rahman, Wahbi; Sudarsono, Sudarsono; Djatmika, Prija; Madjid, Abdul; Rehulina, Rehulina (LAW REFORM, 2024)
The regulation of the criminal accountability system for discretion that causes state losses is governed by Law Number 31 of 1999, as amended by Law Number 20 of 2001 on the Eradication of Corruption. This law includes the element of "abusing authority, opportunity, or means available due to one's position or rank that may cause state financial losses," which can lead to criminal punishment. Additionally, Law Number 30 of 2014 on Government Administration also regulates the imposition of administrative sanctions. The purpose of this research is to analyze the priority mechanism when there is an overlap between administrative and criminal illegality in cases of discretion by government officials that result in state financial losses. This research employs a normative legal method. The findings suggest that, according to current legislation, when a case involves overlapping issues between the Corruption Law and the Government Administration Law, priority should be given to administrative measures based on the Government Administration Law. This approach is aimed at improving orderly government administration and preventing abuse of authority.